2007
DOI: 10.1093/bmb/ldm027
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac adaptation to training and decreased training loads in endurance athletes: a systematic review

Abstract: Studies reported an increase in LVEDD and LVPW, following endurance training. However, the heterogeneity of the studies and the sensitivity of echocardiography technique can be two reasons, for which the results do not allow to state unequivocally that the adaptation to endurance training of highly trained hearts stems from increments of diastolic diameter of the left ventricle and lateral wall of the left ventricle (LVPW).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Lastly, regression of the trained heart back to normal dimensions with training cessation has been identified by various researchers to differentiate training cardiac adaptations from hypertrophic cardiomyopathy. A meta‐analysis that studied the aforementioned regression phenomenon concluded that due to the heterogeneity among studies, it is difficult to indicate how much do dilation and hypertrophy decline when athletes decrease or stop training (Calderon Montero et al ., ).…”
Section: Comparative Analysis Of the Ventricular Function Of An Athlementioning
confidence: 97%
“…Lastly, regression of the trained heart back to normal dimensions with training cessation has been identified by various researchers to differentiate training cardiac adaptations from hypertrophic cardiomyopathy. A meta‐analysis that studied the aforementioned regression phenomenon concluded that due to the heterogeneity among studies, it is difficult to indicate how much do dilation and hypertrophy decline when athletes decrease or stop training (Calderon Montero et al ., ).…”
Section: Comparative Analysis Of the Ventricular Function Of An Athlementioning
confidence: 97%
“…Potassium channels and mitochondrial biogenesis are among the cardiovascular adaptations affected by exercise [5,6]. ATP-sensitive potassium (KATP) channels are expressed in various tissues such as the heart [7].…”
Section: Introductionmentioning
confidence: 99%